Gest??o estrat??gica de pessoas e carreira profissional: estudo de caso - Paix??o, Claudiane Reis da (2015)
This thesis analyzed the strategic management and people and a career in an organization that excels in managing people, according to Aon Hewitt Ranking ??? published annually in the magazine's best in people management. The selected to compose this research organization was COPAGAZ ??? with the only presence in the yearbook since its first edition in 2003. The purpose of the thesis turned identify the alignment between the two constructs ??? Strategic people management and management of career ??? through the comparison between the perception of the professional area of people management and executive management of the organization regarding policies and human resource practices adopted in the organization. The study was designed based on the phenomenological and hermeneutical method and under the approach of qualitative research, exploratory in nature. The strategy adopted was the case study and one for the data collection contemplated are three sources of evidence: (a) semi-structured interviews with the supervisor of human resources and executive management of the organization; (b) the check list - filled with both - relevant to the constructs under consideration; (c) triangulation for data analysis was completed with the other two instruments. Documentary research - represented by the reports provided by the organization - as well as the editions of the referenced directory, included in the period 2003-2013. Observations made in facilities of the organization completed the data collection. All were analyzed for content, comprising the three analysis categories and sub-categories, all related to the topics. The analysis and discussion of the results showed the congruence of theoretical and empirical data as well as the assumptions and theoretical models announced in formatting the thesis, for each of the constructs: the model of vision transformed (strategic management of people); the model of subjective and Proteins careers (career management) and model of system administration career (the interaction between strategic people management and career management). The research question was answered by the evidence of policies and practices related to human resources management career held at Copagaz organization, thanks to a positioning of human resources, in line with the strategic management and therefore considered as strategic people management. The organization does not yet have a formal program aimed at managing career, but the structure of Copagaz ??? in particular their beliefs and organizational philosophy ??? enable them to develop policies aimed at professional development, such as subsidies for scholarships that promote involvement and engagement on the objectives and results of the organization. So says the alignment between the constructs analyzed in this thesis as perceived by the professionals interviewed. In this work suggest if new studies and research about the career, since professional activities represent one of the fields of human achievement. Organizations that excel in managing people demand sustainable management related to the management of people and aligned to career advancement, and professional development for development with mutual gains for individuals and organizations.